Benign lymphoproliferative disorders in the immunosuppressed patient: an update. (24th June 2021) - Robinson, Liam; Fonseca, Felipe Paiva; van Heerden, Willie F. P.
Abstract: Immunosuppressed patients may be affected by a wide range of lymphoproliferative disorders (LPDs) ranging from self‐limiting disorders to malignant lymphoid proliferations. These LPDs may be associated with systemic immune disorders, develop following organ transplantation or occur in the background of other forms of iatrogenic immunosuppression. Lymphotropic viruses, including Epstein‐Barr virus (EBV) and human herpesvirus‐8 (HHV8), have been associated with the pathogenesis of distinct LPDs. The resulting classification of this group of disorders is very complex and inconsistent, with several new and emerging entities. Consequently, the diagnosis of an LPD, especially in an immunosuppressed patient, and its subsequent clinical management usually represent an important pitfall in daily clinical and pathology work. Therefore, the aim of this review was to use the available literature to describe the clinicopathological features of the most important benign LPDs that may be diagnosed in the head and neck region of immunosuppressed patients. Original clinical and microscopic images were used to illustrate some of these entities.